Pengaruh Penggunaan Filter pada Instagram terhadap Sikap Profesionalisme Mahasiswa Tata Rias dalam Menyiapkan Portofolio Hasil Makeup - Zizah Hanaziah; Mimi Yupelmi (STKIP Subang, 2026)
The development of social media has encouraged Cosmetology students to utilize various digital features to publish their makeup work, one of which is the use of Instagram filters. This feature allows users to enhance the visual appearance of photos so that the makeup results appear more attractive when shared with the public. However, excessive use of filters can create a difference between the actual makeup results and their appearance on social media, potentially affecting professionalism in preparing digital portfolios. This study aims to describe the level of Instagram filter use and professionalism of Cosmetology students in preparing makeup portfolios, and analyze the effect of Instagram filter use on this professionalism. This study used a quantitative method with a descriptive associative approach. The population consisted of 84 Cosmetology students from the class of 2022 at Padang State University, all of whom were included as the research sample using a total sampling technique. Data were collected through a Likert-scale questionnaire that met validity and reliability requirements and analyzed using descriptive statistics and a quadratic nonlinear regression model with the help of SPSS software. The results showed that the level of Instagram filter use was in the moderate category, while the students' professionalism in preparing makeup portfolios was in the high category. The regression analysis revealed a significance value of 0.001 (p < 0.05), indicating a significant influence of Instagram filter use on student professionalism. The coefficient of determination (R²) value of 0.155 indicates that Instagram filter use contributes 15.5% to student professionalism, while the remaining 84.5% is influenced by other factors not examined in this study. These findings suggest that Instagram filters should be used appropriately to maintain the visual quality of digital portfolios while ensuring that the work displayed still reflects students' true abilities.